Encyclopedia of African American history, 1896 to the present : from the age of segregation to the twenty-first century - Finkelman, Paul, 1949- (New York : Oxford University Press, 2009)
Focusing on the making of African American society from the 1896 "separate but equal" ruling of Plessy v. Ferguson up to the contemporary period, this encyclopedia traces the transition from the Reconstruction Era to the age of Jim Crow, the Harlem Renaissance, the Great Migration, the Brown ruling that overturned Plessy , the Civil Rights Movement, and the ascendant influence of African-American culture on the American cultural landscape. --publisher description
v. 1. A-C -- v. 2. D-I -- v. 3. J-N -- v. 4. O-T -- v. 5. U-Y, Chronology, Index
Includes bibliographical references and index.
Keywords: African Americans -- History -- Encyclopedias; African Americans -- History -- 1877-1964 -- Encyclopedias; African Americans -- History -- 1964- -- Encyclopedias; African Americans -- Biography -- Encyclopedias; Geschichte 1850-1900.; Geschichte 1900-2000.; Geschichte 2000-2050.; Geschichte 1896-2008.; Schwarze -- United States -- Geschichte 20. Jh -- 2; USA; Schwarze